Interactive E-Flipbook as Digital Learning Innovation in Project-Based Craft Education - Lutfah Raudhotul Jannah; Sita Nurmasitah (Universitas Negeri Semarang, 2026)
The integration of digital media into project-based learning has become increasingly important in supporting creative skill development in secondary education. However, the availability of structured and validated digital learning resources for craft subjects remains limited. This study aimed to develop and validate an e-flipbook learning medium for tote bag painting within project-based craft classes. The research employed a Research and Development (R&D) approach using the ADDIE model, limited to the analysis, design, and development stages. The feasibility of the developed product was evaluated through expert validation using the Content Validity Index (CVI). The validators consisted of three media experts and three subject-matter experts. The results indicated that the media component achieved an S-CVI/Ave value of 0.95 and an S-CVI/UA value of 0.85, both categorized as highly feasible. Meanwhile, the material component obtained an S-CVI/Ave value of 0.90 (very feasible category) and an S-CVI/UA value of 0.69 (feasible category). These findings demonstrate that the developed e-flipbook meets the required content validity standards in both media and material aspects. Therefore, the e-flipbook can serve as a validated digital learning alternative to support project-based craft instruction in secondary education.